Cunoașterea și îndumnezeirea prin Biserica, în gândirea Sfântului Iustin Popovici - Micevski Ilche (Arhiepiscopia Bucureștilor, Facultatea de Teologie Ortodoxă, 2017)
This study is an approach on the thought of St Justin Popovic upon knowledge and theosis through Church. St. Justin Popovic writes about Jesus Christ and the Church as being a single divine-human organism. Jesus Christ is the head of this organism and the Church is the body. The Church is the extension of Christ in eternity and within the Church is possible the union between Man and God. În the Church, knowledge and theosis are being hindered by sin, but advancing în knowledge and theosis is helped by virtues and the Holy Sacraments. Through the Grace obtained within the Church, the mind and reason are being sanctified and this becoming capable of deeper knowledge of the divine mysteries. The human reason gets unified with the divine reason-Jesus Christ- thus getting to know the mysteries of God and of the Creation through Jesus Christ, as possible it can be for a human being.
Anuarul Facultății de Teologie Ortodoxă „Justinian Patriarhul”, 2017
Keywords: St. Justin Popovic, knowledge, church, sacraments, virtues